Pembuatan dan Pelatihan Website Daf Tour Travel - Dwi Harini; Anita Sari Wardani; Arie Nugroho; M. Najibulloh Muzaki; Fredi Pangestu; Rini Indriati; Andriyanto, Teguh (Jurnal Pengabdian Masyarakat Nusantara, 2021)
The business world today is turning to the use of information technology to support e-business, especially the business-to-consumer type. Therefore, business actors are expected to be able to follow the development of the business world. Daftour is a business actor in the field of tourism (tour and travel) who has limited human resources in managing e-business technology information. To overcome these problems in this service activity the author provides a solution, namely the creation and training of the Tour Travel website management. The process of this activity includes needs analysis, content design, domain and hosting purchases, website installation and setting, and website management training. The result of this service activity is a travel tour website that can be used as a promotional media and initial communication with potential customers.